Validation of Optical Structural Alterations in Two Oligodendroglioma Tumors - Kornaus, Andrew (My University, 2011)
Many large- and small-scale changes occur in the genomes of tumor cells. The optical mapping system was used previously to discover structural variations (OSAs; Optical Structural Alterations) in tumor genomes. OSAs are structural variants which include single basepair changes, resulting in missing or extra restriction enzyme sites in the genome, or small insertions and deletions, which can change the local size of individual restriction fragments as well as addition or deletion of entire restriction fragments at a time. OSAs were validated by polymerase chain reaction (PCR) of the regions that differ from reference human sequence and subsequent restriction digest of amplicons to verify the restriction map reported by optical mapping. This study looks at OSAs found in two oligodendrogliomas-tumors that have arisen from oligodendrocytes, the cells that insulate axons within the brain.
19 p.
Keywords: Genetics; Biology